Koala: A Natural History and an Uncertain Future - Clode, Danielle (New York, NY : W.W. Norton & Company, 2023)
"A biologist takes us into the still mysterious world of koalas, from their marsupial ancestors to current threats to their existence. Koalas are one of the most beloved animals, but despite their celebrity, we are just learning much about their nature and history. Blending evolutionary biology, natural history, and ecology, biologist Danielle Clode tells us the story of these amazing marsupials. She looks at fossils of ancestral giant koalas three times modern koalas' size and explains why they are the lone survivor of a once diverse family tree. Clode investigates their nature--often affectionate but can also be belligerent--and their physiology--from their pouches to their gut bacteria, which can only digest leaves of the species of gum tree they were raised on. She also warns about the danger koalas have been in as humans have impinged on their habitats through land clearance and urban development. Now, Australia's explosive wildfires threaten them each summer, killing and harming them as never before. Clode takes us close to these extraordinary creatures and speaks to why and how we need to save them."--
Includes bibliographical references and index.
Keywords: Koala -- Australia; Koala -- Ecology. -- Australia; Koala -- Habitat. -- Australia; Marsupials and monotremes